Vector Mode Analysis of Ring-Core Fibers: Design Tools for Spatial Division Multiplexing - Brunet, Charles; Ung, Bora; Belanger, Pierre-andre; Messaddeq, Younes [UNESP]; Larochelle, Sophie; Rusch, Leslie Ann (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Design tools have existed for decades for standard step-index fibers, with analytical expressions for cutoff conditions as a function of core size, refractive indexes, and wavelength. We present analytical expressions for cutoff conditions for fibers with a ring-shaped propagation region. We validate our analytical expressions against numerical solutions, as well as via asymptotic analysis yielding the existing solutions for standard step-index fiber. We demonstrate the utility of our solutions for optimizing fibers supporting specific eigenmode behaviors of interest for spatial division multiplexing. In particular, we address large mode separation for orbital angular momentum modes and fibers supporting only modes with a single intensity ring.
Keywords: Multiplexing; optical design; optical fibers